It's Time We Looked Under the Hood: An In-Depth Examination of Five Public California Area Agencies on Aging. (15th August 2022) - Gallo, Haley B; Marnfeldt, Kelly Ann; Navarro, Adria E; Wilber, Kathleen H
Abstract: Background and Objectives: As the older adult population grows, it is important to understand the effectiveness of service delivery systems that support aging in place. Studying service delivery processes and organizational structures of Area Agencies on Aging (AAAs) is essential for future efforts to understand service delivery outcomes and innovations. Research Design and Methods: We conducted site visits with 5 government-run California AAAs. We used a template and constant comparative analysis to analyze transcripts from site visits and focus groups with key informants. Results: AAA representatives discussed how their organizational structure was related to (a) which services and programs they provided; (b) administrative cost savings and access to funding sources; (c) inter- and intra-agency coordination; and (d) visibility among clients and community partners. Discussion and Implications: These findings can be used to guide decisions surrounding how changes in AAA structure may affect funding, coordination, service delivery, and visibility, among other factors. Consolidating the AAA with other departments and programs facilitates coordination and shared administrative costs, yet consolidation may reduce standalone AAAs' visibility and ability to innovate. AAA structure should be tailored to fit community resources, local government organization, and the needs of older residents.